DESAIN PERANCANGAN KANTOR AGEN LPG PT. MIGATO - safitri, ikraeni (Gorontalo Journal of Infrastructure and Science Engineering, 2023)
Design is an action in making a decision containing data and information or facts in activities. Activities in planning the development of a business office needed by the community can utilize the available space. One of the businesses that the community really needs is LPG. The purpose of this study is to design the construction of an LPG agent office, PT. Migato. The method used in this study is to use qualitative methods, namely the approach of primary data and secondary data. Primary data obtained from direct field observations, namely field observations, interviews, documentation. While secondary data, namely information containing information from literature studies and literature studies related to grafting. The results of the design of the LPG agent business building PT. Migato is expected to be able to assist the community in facilitating household affairs with the need for gas through a strategic location because it is in a community environment.